Women, veiling and politics : the South Asian conundrum - Conference on Women, Veiling and Politics (2015 : Colombo, Sri Lanka); Ahmed, Imtiaz, 1958-; Regional Centre for Strategic Studies (Colombo, Sri Lanka); Global Partnership for the Prevention of Armed Conflict (Dhaka, Bangladesh : University Press Limited, 2020)
Contributed articles presented at the author's workshop held in October 2015.
Includes bibliographical references and index.
Keywords: Purdah -- South Asia -- Congresses; Veils -- Political aspects -- South Asia -- Congresses; Veils -- Social aspects -- South Asia -- Congresses; Feminist political geography -- South Asia -- Congresses; Conference papers and proceedings